Historical origins of the idea of gender equality - Kholod, Y. A. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
This article is dedicated to the analysis of the formation of the idea of gender equality through the lens of philosophical and legal discourse, with particular attention to its conceptualization within the European intellectual tradition and subsequent normative consolidation. The study examines the core views on the role of women in society as articulated in the works of prominent modern thinkers such as Plato, Jean-Jacques Rousseau, and John Stuart Mill, and traces how these ideas influenced the development of legal consciousness and the emancipation movement. It is demonstrated that philosophical concepts often served both as a source of paternalistic justification for gender hierarchy and as a foundation for revising dominant social perceptions of women as political and legal subjects. Special emphasis is placed on the critical analysis of declarative documents that marked key milestones in the legal recognition of women’s equality, particularly the Declaration of the Rights of Woman and the Female Citizen by Olympe de Gouges (1791) and the Declaration of Sentiments adopted at the Seneca Falls Convention in 1848. Through textual analysis and rhetorical interpretation, it is shown that these documents not only addressed the issue of women’s legal invisibility but also laid the groundwork for further transformations in the realm of civil rights, social progress, and constitutional thought. The article provides a comprehensive reflection on the mechanisms of legitimizing gender equality as a legal category shaped by ethical, social, and philosophical factors. It highlights the role of discursive strategies in the development of a feminist legal paradigm, in which the rhetoric of justice, moral autonomy, and equal access to institutions of power occupies a central place. Using a historical-comparative approach, the study reveals the connection between philosophical notions of equality and the normative framing of women’s rights in later legal documents. The evolution of female legal subjectivity, the formation of political feminism, the struggle for inclusivity, participation in politics, labor law reform, and the issue of social discrimination are all explored. The article aims to deepen theoretical understanding of the evolution of gender equality as a socio-legal phenomenon, emphasizing its interdisciplinary nature and its importance for building a democratic rule-of-law state.